2011
DOI: 10.1093/icvts/ivr038
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis with cerebrovascular complications: timing of surgical intervention

Abstract: Management of infective endocarditis (IE) with cerebrovascular complications is difficult due to absence of concrete evidence. These patients usually have multiple neurological deficits and the optimal timing for cardiac operation remains controversial. The aims of this study were to present cases and discuss the treatment options for IE with cerebrovascular complications. From 1998 to 2010, 51 patients underwent operations for IE at our institution. From a review of medical records, 10 patients (19.6%) with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…5,13 This complication is rare, occurring in around 2-4% of cases, and as reported, more than half (57.4%) are located in the distal branches of the medium cerebral artery. 7,13,14,15 The cerebral hemorrhage presented by the patient can be justified by the fact that mycotic aneurysms generally present a fine and fragile wall. 7 A multicenter study conducted in France showed that 65-80% of mycotic aneurysms are asymptomatic, diagnosed only by imaging exams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,13 This complication is rare, occurring in around 2-4% of cases, and as reported, more than half (57.4%) are located in the distal branches of the medium cerebral artery. 7,13,14,15 The cerebral hemorrhage presented by the patient can be justified by the fact that mycotic aneurysms generally present a fine and fragile wall. 7 A multicenter study conducted in France showed that 65-80% of mycotic aneurysms are asymptomatic, diagnosed only by imaging exams.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rupture, however -as in the case presented here, in which the patient experienced convulsions and changes to her level of consciousness -, mortality reaches 80%. 5,10,11,14,16 In contrast with ruptured aneurysms, unruptured ones have a much lower mortality rate (30%) and treatment is generally based on antibiotics and patient monitoring. 5,14 In addition to the difficulty in diagnosis, the treatment of this complication does not yet have defined protocols, which makes conduct individualized and based on the clinical symptoms of the patient, as well as on the cost-benefit analysis of the treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13) Patients were examined according to our IE management algorithm. 12) Cerebral computed tomography (CT) was systematically performed on admission and antibiotic therapy was started immediately after diagnosis. Cerebrovascular complications included cerebral infarction, cerebral hemorrhage, intracranial mycotic aneurysm, brain abscess and meningitis.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective randomized assessments of the proposed plans have also been lacking. We have developed an algorithm for the management of IE patients 12) and have applied this algorithm to all IE patients treated in our institution since 2002. In this study, we summarized the clinical characteristics, pathology and surgical outcomes within a comparison between IE patients with cerebrovascular complication (CVC) and without CVC.…”
Section: Management Of Infective Endocarditis With Cerebral Complicatmentioning
confidence: 99%